Kinematics and dynamics study of a hexapod robotic system using computational packages’ capabilities - Flores, Paulo (2007)
The main purpose of this work was to perform kinematics and dynamics analysis of a prototype of an autonomous hexapod robot. This paper reports on an initial phase, where the basic geometry of the system was specified and improved through a kinematics and dynamic study by using a motion analysis software. This study also allowed the design of all mechanical components and the definition of motion generation needs. In this paper the importance of legged robots on mobile research is emphasised. The capabilities of the computational programs specially dedicated to the analysis of mechanical systems are also discussed. The mobility of the geometric model presented in this paper is a trade-off between natural idea and technical feasibility. Some results of the computational simulations of the movement of the proposed hexapod robotic system are presented and discussed under the premises and assumptions adopted in this work.